‘Not A Sufficient Reason’: LGBTQ asylum seekers in the Russian asylum system - Rosolovskaya, Ekaterina (Anti-Trafficking Review, 2022)
This article provides an analysis of the Russian asylum system with a specific focus on its treatment of LGBTQ asylum seekers. I analysed existing literature on the Russian asylum system and examined asylum decisions from first-instance and second-instance immigration authorities and appeal decisions issued by the Basmanny district court of Moscow and the Moscow city court. While there seems to be no unified approach as to whether LGBTQ asylum seekers constitute a particular social group in the sense of the UN Refugee Convention, there is a consistent trend of refusing international protection to LGBTQ asylum seekers at all levels. The relevant bodies either ignore the systematic persecution LGBTQ persons face in the countries of origin or simply dismiss the arguments put forward by the applicants and conclude that there is no proof of the existence of personal risks in case of return. Such an approach further pushes the applicants into a semi-underground existence.